Transition between canonical to non-canonical Wnt signaling during interactions between mesenchymal stem cells and osteosarcomas - Masha Asulin; Noa Ben Ghedalia-Peled; Ifat Cohen Erez; Yvonne Ventura; Razi Vago (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2020)
Background: Wnt signaling pathways are taking a part in regulation of cell fate decisions in normal and cancerous cells. In some cancer types, a transition from canonical to non-canonical Wnt signaling pathways was identified, a phenomenon, that in return led to increase proliferation, invasiveness and metastasis.  Methods: In the current in vitro study we investigated the influence of MSCs, co-cultured in direct and indirect contact with OS cells, on the role of Wnt signaling pathways and tumor aggressiveness. Sub-populations were separated using Boyden chambers. Gene expression profiles were determined by qPCR.  Results: The results revealed that interactions with MSCs increased migration and invasion capacities along with OS proliferation. Moreover, canonical Wnt signaling activity was low in OS, and co-culture with MSC. However, MSCs did not trigger a switch between the canonical to the no-canonical Wnt pathways. In addition, a more aggressive OS sub-population tend to undergo a transition towards the non-canonical pathway. Moreover, this aggressive subtype presented cancer stem-cells like characteristic. Conclusions: We submit that the progression in OS aggressiveness is attributed to a transition in Wnt signaling from canonical to non-canonical pathways, although MSCs are likely to take a part during the tumor progression, in the case of OS, they did not affect the Wnt switch. These complex tumor promoting interactions may be found in the natural and tumorigenic bone microenvironment. A better understanding of the molecular signaling mechanisms involved in the tumor development and metastasis may contribute to development of new cancer therapies.